Hubungan Kelincahan dan Koordinasi Mata Tangan Dengan Ketepatan Forehand Drive Tenis Meja Pada Peserta Didik Ekstrakurikuler MAN 1 Mandailling Natal - Lubis, Ahmad Danil; argantos, argantos; yendrizal, yendrizal; haryanto, jeki (Universitas Negeri Padang, 2025)
This study discusses the relationship between agility and hand-eye coordination with the accuracy of table tennis forehand drive in extracurricular students of MAN 1 Mandailing Natal. The purpose of the study was to examine the relationship between agility and hand-eye coordination with the accuracy of table tennis forehand drive in extracurricular students of MAN 1 Mandailing Natal. The study used correlational research. The population of this study were students who participated in table tennis extracurricular activities at MAN 1 Mandailing Natal. Sampling using total sampling technique totaling 20 male students. Data were collected through field tests and documentation. The data analysis technique in this study used the analysis prerequisite test consisting of normality test, homogeneity test, and hypothesis test consisting of simple correlation test and multiple correlation test. The results of the data analysis show that: (1) There is a significant relationship between agility and accuracy of iable tennis forehand drive in extracurricular students of MAN 1 Mandailing Natal, obtained asig result iof 0.035 and an ir value of 0.473, which means the relationship is quite close. (2) There is a significant relationship between hand-eye coordination iand iaccuracy of table tennis forehand drive in extracurricular students of MAN 1 Mandailing Natal, obtained a sig result of 0.018 and an r value of i0.524, which means the relationship is quite close. (3) There is a significant relationship between agility and hand-eye coordination together with accuracy of table tennis forehand drive in extracurricular students of MAN 1 Mandailing Natal, obtained a sig result of F 0.015, where the isign is <0.05 with an r value of 0.625, which means the relationship is high. Keywords: Agility, hand eye coordination, forehand drive accuracy, table tennis